The Effect of Health Education about Low Purine Diet through Video Media on the Level of Knowledge of Gout Patients - Ningsih, Tri Hadi; Yuniartika, Wachidah (Indonesian Journal of Global Health Research, 2024)
Gout is a disease caused by the accumulation of monosodium grate crystals in the human body. The cause of the high incidence of gout is a lack of knowledge about preventing gout, so efforts can be made with Health Education to increase understanding. This research aims to determine the effect of health education about a low-purine diet delivered through video media on the level of knowledge among gout sufferers. This quantitative research employs a quasi-experimental study design, specifically a "one-group pretest-posttest design." A total of 33 respondents were selected to assess their level of knowledge using a questionnaire obtained through accidental sampling. Data collection involved distributing questionnaires to respondents (pretest), where the questionnaire had undergone a validity test with a result of r- calculated > r-table (0.632) and a reliability test with a Cronbach's alpha value of 0.978 therefore, the questionnaire was declared valid and reliable, after which the researchers provided health education regarding a low-purine diet. The questionnaire was then distributed again to the respondents (posttest). The data analysis utilized the Wilcoxon Signed Ranks Test. The Wilcoxon Ranks test produced statistically significant values (sign. = 0.00 < 0.05). The findings of this study indicate that health education about a low-purine diet delivered through video media influences the level of knowledge among gout sufferers.